Current Aspects of Formulation Efforts and Pore Lifetime Related to Microneedle Treatment of Skin - Milewski, Mikolaj (2010)
IMPORTANCE OF THIS FIELD: The efficacy of microneedles in the area of transdermal drug delivery is well-documented. Multiple studies have shown that enhancement of skin permeation via creation of microscopic pores in the stratum corneum can greatly improve the delivery rates of drugs. However, skin pretreatment with microneedles is not the only factor affecting drug transport rates. Other factors including drug formulation and rate of micropore closure are also important for optimizing delivery via this route. AREAS COVERED IN THIS REVIEW: This review aims at highlighting work that has been done in these areas, with an emphasis on drug formulation parameters that affect transdermal flux. WHAT THE READER WILL GAIN: This review creates an appreciation for the many factors affecting microneedle-enhanced delivery. Most results clearly indicate that microneedle skin pretreatment by itself may have different effects on drug transport depending on the formulation used, and formulation characteristics have different effects on the transport through untreated skin and microneedle-treated skin. Several formulation approaches are reported to optimize microneedle-enhanced drug delivery, including cosolvent use, vesicular, nanoparticulate and gel systems. TAKE HOME MESSAGE: In addition to well-established factors that affect microneedle-assisted delivery (geometry, type of microneedles, etc), formulation and pore viability are also critical factors that must be considered.